1997
DOI: 10.2527/1997.75123294x
|View full text |Cite
|
Sign up to set email alerts
|

Limiting amino acids in meat and bone and poultry by-product meals.

Abstract: ABSTRACT:In situ, digestion, and growth studies were conducted to evaluate four meat and bone meals and six poultry by-product meals as sources of escape protein and to predict the first-limiting amino acid for growing calves. Escape protein values, determined by 12-h in situ incubation, ranged from 41.7 to 51.0% of CP for meat and bone meals; poultry by-product meals ranged from 32.0 to 39.8%. True protein digestion in the gastrointestinal tract of lambs differed among protein sources ( P < .05), ranging from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
2
18
0
1
Order By: Relevance
“…Analysis of the residue following incubation was chosen because Varvikko (1986) and Crooker et al (1981) reported that certain amino acids were more resistant to microbial degradation than others. Likewise, Klemesrud et al (1997b) reported that amino acid profiles of dietary protein were altered during in situ incubation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis of the residue following incubation was chosen because Varvikko (1986) and Crooker et al (1981) reported that certain amino acids were more resistant to microbial degradation than others. Likewise, Klemesrud et al (1997b) reported that amino acid profiles of dietary protein were altered during in situ incubation.…”
Section: Resultsmentioning
confidence: 99%
“…Residue remaining after incubation was composited by protein source and analyzed for amino acid content (Klemesrud et al, 1997b). Samples were hydrolyzed in 6 N HCl, and amino acid content of hydrolyzates was determined with ion-exchange chromatography (AOAC, 1984).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ruminal undegraded protein (RUP) for the protein sources was determined following 12 h (O'Mara et al 1997;Klemesrud et al 1997). Duplicate samples of each protein source were weighed into nylon bags (9 × 12 cm; 41 µm pore size) and incubated in the rumen of a ruminally fistulated non-lactating Holstein cow for 12 h. Following removal from the rumen, the bags were rinsed in tap water and dried at 55°C for 48 h.…”
mentioning
confidence: 99%